Boronizing of pure niobium - Usta, Metin; Özbek, Ibrahim; Ipek, Mediha; Bindal, Cuma; Üçişik, Ahmet Hikmet (My University, 2004)
This study reports on bonding possibility of pure niobium (Nb). Bonding was carried out at 940°C for 2-8 h. XRD analysis revealed that the dominant phase formed in coating layer is NbB2. Optical cross-sectional image of borided Nb showed that borides formed on the surface of Nb has a smooth and compact morphology. The hardness of borides measured by means of Vickers indenter is over than 2000 HV. © 2008 Elsevier B.V., All rights reserved.
Transactions - 7th World Biomaterials Congress -- Sydney -- 64310
Keywords: Biocompatibility; Borides; Boriding; Coating techniques; Electric resistance; Electrochemistry; Hardness; Microscopic examination; Morphology; Strength of materials; Surface treatment; Vickers hardness testing; X ray diffraction analysis; Electrochemical properties; Hard borides; Microhardness tester; Pure niobium; Niobium